Obtenção e caracterização do produto seco da pimenta rosa (Schinus terebinthifolius R.) por cast tape drying - Pich, Raquel Clasen (2019)
Pink pepper is a native Brazilian fruit produced commercially in the state of Espírito Santo, which has medicinal properties such as antioxidant, healing, antitumor and antimicrobial activity. Drying is traditionally defined as the unitary operation that converts a solid, semi-solid or liquid material into a solid product of considerably low moisture. In general, water removal occurs by evaporation and involves the application of thermal energy, which causes the phase change from liquid to vapor. The research suggest that active aromatic and pigmentary compounds responsible for sensory and nutritional attributes, characteristic of food, can be retained through cast-tape drying (CTD). CTD drying is an alternative process for drying fruit and vegetable pulps, operating at moderate temperatures, resulting in relatively small drying times. The objective of this work is to obtain and characterize physically-chemically the powder of the pink pepper fruits (Schinus terebinthifolius Raddi) dehydrated by cast-tape drying. This study is divided into two parts, the first covers the study of the appropriate size reduction methodology fruits of the pink pepper, in which the results demonstrated that the blanching of the fruits and the later grinding in knife mill is the most appropriate methodology of preparation of the pink pepper for drying; the second one covers the study of the drying kinetics of the samples and the evaluation of the influence of the process conditions, sample thickness and circulating water temperature in the drying kinetics. The results suggest that 95 °C and 2 mm is the combination of conditions that achieved the lowest drying time, the lowest humidity and the lowest water activity of the powders produced. The scanning electron microscopy (SEM) images showed the irregularity of the particles of the powders produced by CTD.